Van Der Pol Central Pattern Generator (VDP-CPG) model for quadruped robot - Jasni, Farahiyah; Shafie, Amir Akramin (2012)
he Central Pattern Generators (CPGs) are becoming a popular method as the alternative control mechanism replacing the conventional trajectory-based method for designing the locomotion gait of mobile robot nowadays. CPG is described as a set of neural networks that have the ability to produce rhythmic movements, such as walking, swimming and flying without intervention from the sensory inputs and higher level control. This paper aims to highlight the efficiency of the biologically inspired, VDP-CPG based control method in modelling the walking gait for a quadruped robot. A new approach of VDP-CPG based walking gait model is developed in which 3-D foot trajectories are generated by mapping the output from CPG. The simulated foot trajectories of the CPG-based control and conventional trajectory-based method are compared to confirm the performance.